GEOMETRIC MODELLING AND SIMULATION ON HEAT TRANSFER PROBLEMS - Mohammad Izat Emir Zulkifly, editor 639043; Ahmad Fadillah Embong, editor 639044; Mohammad Izat Emir Zulkifly, contributor 639043; Ahmad Fadillah Embong, contributor 639044; Yeak, Su Hoe, 1971-, contributor 553892; Nur Adlin Lina Normisyidi, contributor 639045; Suzarina Ahmed Sukri, 1993-, contributor 606142; Taufiq Khairi Ahmad Khairuddin, contributor 611556; Alifah Ilyana Abdul Aziz, contributor 639046; Nur Farhanah Zaidi, contributor 639047; Abd. Fatah Wahab, contributor 639048; Mohd. Shafiq Bidin, contributor 639049; et al. (Johor Bahru, Johor: PENERBIT UTM PRESS, 2021)
Includes bibliographies and index.